2016
DOI: 10.5483/bmbrep.2016.49.12.169
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of 3-(naphthalen-2-yl(propoxy)methyl)azetidine hydrochloride on hypoxia-induced toxicity by suppressing microglial activation in BV-2 cells

Abstract: We recently reported the anti-inflammatory effects of 3-(naphthalen-2-yl(propoxy)methyl)azetidine hydrochloride (KHG26792) on the ATP-induced activation of the NFAT and MAPK pathways through the P2X7 receptor in microglia. To further investigate the underlying mechanism of KHG26792, we studied its protective effects on hypoxia-induced toxicity in microglia. The administration of KHG26792 significantly reduced the hypoxia-induced expression and activity of caspase-3 in BV-2 microglial cells. KHG26792 also reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Briefly, cells were plated at a density of 5 × 10 5 cells in 96-well plates, and the extracellular and intracellular amounts of LDH were determined with the LDH toxicity detection kit from the Roche (Mannheim, Germany) according to the manufacturer’s instructions. MTT assay was performed to determine cell viability by quantifying the color formation at 595 nm with an enzyme-linked immunosorbent assay (ELISA) microplate reader as described before ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, cells were plated at a density of 5 × 10 5 cells in 96-well plates, and the extracellular and intracellular amounts of LDH were determined with the LDH toxicity detection kit from the Roche (Mannheim, Germany) according to the manufacturer’s instructions. MTT assay was performed to determine cell viability by quantifying the color formation at 595 nm with an enzyme-linked immunosorbent assay (ELISA) microplate reader as described before ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…TNF-α, IL-6, and IL-1β levels were measured using commercial ELISA kits (R&D Systems, Minneapolis, MN) according to the manufacturer’s instructions, as previously described ( 3 , 11 ). The optical density was detected with a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a previous study also showed the memory-restorative effect of ezetimibe, a well-known azetidine derivative, in memory dysfunctions associated with Alzheimer’s disease dementia ( 10 ). Previously, we synthesized 3-(naphthalen-2-yl(propoxy)methyl)azetidine hydrochloride (KHG26792) and reported that KHG26792 significantly decreased hypoxia-induced toxicity by attenuating oxidative stress ( 11 , 12 ). However, the precise mechanisms for the action of KHG26792 have not been elucidated, particularly for MPP + -induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%